The Floodscale experiment in the small catchment of Valescure, France: An overview of the isotopic and geochemical data base. (29th October 2018) - Bouvier, Christophe; Patris, Nicolas; Freydier, Rémi; Guilhe‐Batiot, Christelle; Seidel, Jean‐Luc; Taupin, Jean‐Denis; Brunet, Pascal; Remes, Aurore
Abstract: A 3‐year survey has been performed in the Cévennes mountain area, in the South of France, in order to separate surface, shallow sub‐surface and groundwater contributions to the flash flood processes. Electrical conductivity, temperature, pH, major and trace elements, total organic carbon and stable isotopes of water were monitored during low flows and floods, in the small (3.9 km 2 ) granitic catchment of Valescure (Gard, France). The data collected during the campaign are widely presented, in relation to the different hydrological compartments (rainfall, shallow soil water, groundwater, streamwater). This constitutes at present the most complete hydrogeochemical database in the Cévennes area, available within the Hymex data basehttps://mistrals.sedoo.fr/HyMeX/ (Valescure chemistry and water isotopes), DOI of the referenced dataset:https://doi.org/10.6096/MISTRALS-HyMeX.1406 . Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available at DOI10.6096/MISTRALS-HyMeX.140657 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .